Fiscal policy in a monetary economy with capital and finite lifetime - Barbara Annicchiarico; Nicola Giammarioli; Alessandro Piergallini (European Central Bank (ECB), 2006)
This paper develops a dynamic stochastic general equilibrium model with nominal rigidities, capital accumulation and finite lifetimes. The framework exhibits intergenerational wealth effects and is intended to investigate the macroeconomic implications of fiscal policy, which is specified by either a debt-based tax rule or a balanced-budget rule allowing for temporary deficits. When calibrated to euro area quarterly data, the model predicts that fiscal expansions generate a tradeoff in output dynamics between short-term gains and medium-term losses. It is also shown that the effects of fiscal shocks crucially depend upon the conduct of monetary policy. Simulation analysis suggests that balanced-budget requirements enhance the determinacy properties of feedback interest rate rules by guaranteeing inflation stabilization.
Keywords: E52; E58; E63; 330; Capital Accumulation; Finite Lifetime; Fiscal Policy; monetary policy; nominal rigidities; Simulations; Finanzpolitik; Geldpolitik; Theorie; EU-Staaten